2002
DOI: 10.1002/ana.10322
|View full text |Cite
|
Sign up to set email alerts
|

Eubaric hyperoxemia and experimental cerebral infarction

Abstract: We explore three questions concerning arterial hyperoxygenation and focal ischemia. (1) Does greater benefit accrue with higher levels of arterial hyperoxemia? (2) Is the net effect of continuous (intraischemic plus postischemic) oxygen therapy toxic, or beneficial to middle cerebral artery infarction? (3) In view of free radical theories of reperfusion injury, does hyperoxia isolated to the reperfusion period damage tissue? Rats subjected to transient, focal, normothermic, normoglycemic ischemia were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 49 publications
5
61
0
Order By: Relevance
“…There is growing evidence that normobaric oxygen therapy (NBO) is a promising treatment strategy to improve outcome after acute ischemic stroke (Flynn and Auer, 2002;Kim et al, 2005;Singhal et al, 2002a, b). This study substantially extends these prior findings by evaluating different treatment durations, cell-death pathways as well as regional tissue susceptibility to ischemia in two different rat models of focal cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence that normobaric oxygen therapy (NBO) is a promising treatment strategy to improve outcome after acute ischemic stroke (Flynn and Auer, 2002;Kim et al, 2005;Singhal et al, 2002a, b). This study substantially extends these prior findings by evaluating different treatment durations, cell-death pathways as well as regional tissue susceptibility to ischemia in two different rat models of focal cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen therapy can enhance free radical formation that may promote lipid peroxidation, blood-brain barrier integrity breakdown, glutamate-induced excitotoxic cell death, neuroinflammation, and increase brain hemorrhage, particularly when combined with reperfusion (Aronowski et al, 1997;Dubinsky et al, 1995;Elayan et al, 2000;Kent et al, 2001;Kim et al, 2005;Mink and Dutka, 1995). Nevertheless, several experimental studies showed impressive reductions in stroke lesion volumes with normobaric hyperoxia (NBO) (Flynn and Auer, 2002;Kim et al, 2005;Miyamoto and Auer, 2000;Singhal et al, 2002a, b). Most importantly, hyperoxia salvaged ischemic brain tissue without increasing the risk of oxygen free-radical injury (Kim et al, 2005;Singhal et al, 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…Our present findings demonstrating reduced hippocampal protein tyrosine nitration and retention of PDHC enzyme activity with normoxic resuscitation support the need for additional preclinical and clinical studies to resolve this issue. The concept that hyperoxia worsens oxidative tissue damage and neurologic outcome after acute brain injury may not, however, apply to other forms of injury, e.g., stroke and trauma, as evidence suggests that hyperoxia can under some circumstances be beneficial [73][74][75][76][77]. The time during which the brain is exposed to high O 2 can also determine whether hyperoxia is helpful or detrimental.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…3 A recent in vivo electron paramagnetic resonance oximetry study has shown that NBO significantly increases ptiO 2 in "penumbral" brain tissue. 15 In rodents, NBO therapy during transient focal stroke attenuates diffusion-weighted MRI (DWI) abnormalities, stroke lesion volumes, and neurobehavioral outcomes 4,16,17 without increasing markers of oxidative stress. 16 Based on preclinical results, we conducted a pilot clinical study to examine the risks and benefits of NBO in stroke.…”
mentioning
confidence: 99%